Cost calculation of an altruistic act for the plasmids-in-bacteria system through probabilistic simulations (2020)
Multilevel selection is a mechanism that enables natural selection to establish cooperation when competition happens at various levels of the population. Such mechanism can be observed in the system of plasmids in bacteria. Therefore, for this research the cost of altruism will be calculated under the multilevel selection framework for this particular system. In general terms, cooperation can be evidenced in this system when a given plasmid type adopts a relatively low replication rate compared to its contenders. Such strategy inherently translates into a disadvantage at an individual level. However, it represents a benefit at the collective level, since a lower metabolic burden is exerted on the bacterial host. Consequently, to reduce the replication rate can be interpreted as an altruistic act. In particular, for this project an approach based on probabilistic simulations is used to calculate the cost of this act, because it allows to analyze the competition happening between plasmids at an intracellular level. As part of the results, it was found that the cost of an altruistic act depends on the degree of selfishness of the direct contender. Also, it was discovered that the cost paid by a selfish type is negative, which allows for the cost to be interpreted as a benefit in this case. Additionally, a phenomenological expression for the cost of an altruistic act was derived from the results obtained. Such expression shows that the cost is equal to the logarithmic difference between the repression coefficients (or steady-states) of the competing plasmids, multiplied by a constant that is directly proportional to the Hill coefficient. Therefore, this research provides a powerful tool to obtain the cost of an altruistic act through information that can be readily measured on the biological system